Clap your hands - Cauley, Lorinda Bryan (New York : Putnam, 1992)
Rhyming text instructs the listener to find something yellow, roar like a lion, give a kiss, tell a secret, spin in a circle, and perform other playful activities along with the human and animal characters pictured.
Publishers Weekly Editors' Choice
School Library Journal
1.6
K-3
Keywords: Play -- Fiction; Animals -- Fiction; Stories in rhyme; Play -- Fiction; Animals -- Fiction; Stories in rhyme